1972
DOI: 10.1007/bf01401876
|View full text |Cite
|
Sign up to set email alerts
|

A study of electrical impedance of oedematous cerebral tissue during operations

Abstract: In 11 patients, most of whom h~d cerebral tumours, electrical impedance was recorded during the introduction of an impedance electrode during operation. After removal of the lesion impedance was measured in the tissue adjacen~ to the walls of the wound cavity. The readings were correlated with water and electrolyte content and with histological findings in tile specimens taken from the same places. Electrical impedance appeared to be lowered in regions invaded by tumour and also in the surrounding oedematous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…These values represent 46 and 33 % of total tissue water content which is consistent with morphological and physiological evidence of a greatly enlarged extracellular space 11,16 It is of interest to note that the calculated calcium content of oedema fluid was almost five times higher than the calcium activity of extracellular fluid, as determined with ion sensitive electrodes 13,25 In view of the multiple biological actions of calcium even a minor change of ionized calcium induced by the accumulation of oedema fluid could have considerable pathophysiological consequences. In the intact brain calcium is almost exclusively located in the extracellular compartment because powerful ion exchange mechanisms maintain an intra-/extracellular gradient of more than 1:10 40).…”
Section: Discussionsupporting
confidence: 86%
“…These values represent 46 and 33 % of total tissue water content which is consistent with morphological and physiological evidence of a greatly enlarged extracellular space 11,16 It is of interest to note that the calculated calcium content of oedema fluid was almost five times higher than the calcium activity of extracellular fluid, as determined with ion sensitive electrodes 13,25 In view of the multiple biological actions of calcium even a minor change of ionized calcium induced by the accumulation of oedema fluid could have considerable pathophysiological consequences. In the intact brain calcium is almost exclusively located in the extracellular compartment because powerful ion exchange mechanisms maintain an intra-/extracellular gradient of more than 1:10 40).…”
Section: Discussionsupporting
confidence: 86%
“…For Subject 2 the corresponding values were , , and and thus also within the expected range. Conductivities of CSF, skin, and bone were considered isotropic and assigned corresponding in vivo estimates of 1.654 S/m, 0.465 S/m and 0.010 S/m [ 26 , 44 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous investigators have suggested that cerebral impedance measurements change with water content of the brain (Van Harreveld et a/. 1961a/. , Go et a/.…”
Section: Introductionmentioning
confidence: 99%